Ethically Challenging Issues in Business Interpreting: Learning How to Face Cultural Quandaries Through Practice and Reflection - Torrella Gutiérrez, Carmen; Vigier-Moreno, Francisco Javier (Vertimo studijos, 2023)
In business interpreting training, there is the need to train prospective interpreters in professional ethics and conduct, since tenets assumed in other interpreting domains such as impartiality and wholeness may conflict with the interests and needs of the business hiring the interpreter’s services and therefore place the interpreter in an ethical dilemma. In this article, we show how examples of ethically challenging elements extracted from a real interpreter-mediated business meeting corpus (in particular, issues related to culture clashes) can be addressed in business interpreting training. Trainee interpreters are exposed to these situations, which are previously introduced in (semi-)structured roleplays that are then used in the training sessions, and the following subsequent feedback and discussion allow trainees and trainers to explore and expound different options that both transmit the correct message and, more importantly, adhere to professional principles and protocols.
Keywords: ethics; business interpreting; interpreter training; culture clash; cultural differences